Reaching the steady state: 30 years of Anguillicola crassus infection of European eel, Anguilla anguilla L., in Northern Germany - Patrick Unger; Johanna Schmidt; Malte Dorow; Sören Möller; Harry Wilhelm Palm (Parasitology, 2024)
A 30 years long data series on the infection dynamics of European eel (Anguilla anguilla L.) with the non-native invasive nematode Anguillicola crassus Kuwahara, Niimi & Hagaki, 1974 is presented. Parasite burden was evaluated for 30 years in inland and coastal waters in Mecklenburg-Western Pomerania from 1991 to 2020. The total prevalence, mean intensity and damage status of the swim bladders were very high during the first decade (1991–2000), and significantly decreased in both marine and freshwater eel populations in the following decades (2001–2010, 2011–2020). The parasite intensity of eels in coastal waters was significantly lower compared with the freshwater systems (61.3% vs 79.5% in the first decade), indicating the vulnerability of the parasites to brackish water conditions and the fact that the life cycle of A. crassus cannot be completed under high saline conditions. Eel caught in the western part of the Baltic Sea (west of Darss sill) had the lowest mean infection (51.8% in first decade) compared to the eastern part with 63.8%. Thus, besides different infection patterns caused by the environmental conditions, a temporal trend towards a reduced parasite intensity and a more balanced parasite–host relationship developed in the 30 years of interaction after the first invasion. Possible reasons and mechanisms for the observed trends in parasite–host interactions are discussed.